An Evaluation of Control Objective for Information Related Technology (COBIT) 4.0 or 4.1: Systematic Literature Review - Wabiser, Yan Dirk; Singgalen, Yerik Afrianto (Journal of Information Systems and Informatics, 2022)
Control Objective for Information Related Technology (COBIT 4.0 and 4.1) is one of Indonesia’s most popular information technology audit frameworks. This article compares the maturity level of implementing information systems in Indonesia, especially government agencies, educational institutions, health institutions, and companies. The method used is a literature study of the research results from 2015-to 2020 related to COBIT 4.0 and COBIT 4.1. This study’s results indicate that the conceptual framework of COBIT 4.1 is more dominant than COBIT 4.0. The Plan and Organize (PO) domain and the Delivery and Support (DS) domain are mainly used to focus studies on government agencies and companies. Meanwhile, the maturity level is dominated by the repeatable but intuitive (level 2) and defined process (level 3), which can be repeated and defined. Thus, studies on information system audit using the COBIT 4.0 and 4.1 conceptual frameworks need to be improved in education and health agencies or other agencies that integrate business processes with information technology.